The econometrics of complex survey data : theory and applications - Huynh, Kim P.; Jacho-Chávez, David; Tripathi, Gautam (Advances in econometrics ;, 2019)
This volume of Advances in Econometricscontains a selection of papers presented at the "Econometrics of Complex Survey Data: Theory and Applications" conference organized by the Bank of Canada, Ottawa, Canada, from October 19-20, 2017. The papers included in this volume span a range of methodological and practical topics including survey collection comparisons, imputation mechanisms, the bootstrap, nonparametric techniques, specification tests, and empirical likelihood estimation using complex survey data. For academics and students with an interest in econometrics and the ways in which complex survey data can be used and evaluated, this volume is essential